On the unsteady flow of two visco-elastic fluids between two inclined porous plates. (1992) - Sengupta, P. R.; Ray, T. K.; Debnath, L.
Abstract : This study is concerned with both hydrodynamic and hydromagnetic unsteady slow flows of two immiscible visco-elastic fluids of Rivlin-Ericksen type between two porous parallel nonconducting plates inclined at a certain angle to the horizontal. The exact solutions for the velocity fields, skin frictions, and the interface velocity distributions are found for both fluid models. Numerical results are presented in graphs. A comparison is made between the hydrodynamic and hydromagnetic velocity profiles. It is shown that the velocity is diminished due to the presence of a transverse magnetic field.